BUILDING A "SURE ACTUAL" IMMIGRATION ORGANIZATIONAL CULTURE CREATING "SURE ACTUAL" ORGANIZATION CULTURE IN IMMIGRATION - Anggiat Napitupulu; Sohirin Sohirin; Bobby Briando (Jurnal Ilmiah Kajian Keimigrasian, 2019)
This study aims to develop a concept of Immigration’s organizational culture known as “PASTI AKTUAL”, the acronym for Professional, Accountable, Sinergy, Transparent, and Innovative. While AKTUAL stands for Active, Creative, Trusted, Prominent, Credential and Logic. This article uses a qualitative descriptive approach. The data are collected from various literatuures and resources such as scientific journals, relevant book, and other academic resources. The results of the study shows that the organizational culture based on “PASTI AKTUAL” has been accordance with Immigration core values and organizational vision. However, to internalize these values into individual action in order to creating new organizational culture, Immigration needs a role model in leadership, effective communication, appropriate training, and practical action.